Fine‐scale seascape genomics of an exploited marine species, the common cockle Cerastoderma edule, using a multimodelling approach. (24th February 2020) - Coscia, Ilaria; Wilmes, Sophie B.; Ironside, Joseph E.; Goward‐Brown, Alice; O'Dea, Enda; Malham, Shelagh K.; McDevitt, Allan D.; Robins, Peter E.
Abstract: Population dynamics of marine species that are sessile as adults are driven by oceanographic dispersal of larvae from spawning to nursery grounds. This is mediated by life‐history traits such as the timing and frequency of spawning, larval behaviour and duration, and settlement success. Here, we use 1725 single nucleotide polymorphisms (SNPs) to study the fine‐scale spatial genetic structure in the commercially important cockle species Cerastoderma edule and compare it to environmental variables and current‐mediated larval dispersal within a modelling framework. Hydrodynamic modelling employing the NEMO Atlantic Margin Model (AMM15) was used to simulate larval transport and estimate connectivity between populations during spawning months (April–September), factoring in larval duration and interannual variability of ocean currents. Results at neutral loci reveal the existence of three separate genetic clusters (mean F ST  = 0.021) within a relatively fine spatial scale in the north‐west Atlantic. Environmental association analysis indicates that oceanographic currents and geographic proximity explain over 20% of the variance observed at neutral loci, while genetic variance (71%) at outlier loci was explained by sea surface temperature extremes. These results fill an important knowledge gap in the management of a commercially important and overexploited species, bringing us closer to understanding the role of larval dispersal in connecting populations at a fine geographic scale.